Zakat as a Sustainable and Effective Strategy for Poverty Alleviation: from the Perspective of a Multi-Dimensional Analysis - Nafiah Ariyani (Center of Strategic Studies (PUSKAS) BAZNAS, 2016)
Zakat is believed to be an alternative solution to overcome the problems of socioeconomic inequality and particularly poverty. Zakat has been widely practiced in the Islamic world for centuries; however, in order to measure the effectiveness of the system we need support of the empirical facts. This study aims to determine the effectiveness of poverty alleviation patterns based on zakat compared with the pattern of poverty alleviation efforts run by the government and the pattern of Corporate Social Responsibility (CSR), as well as the key determinant factors. Measurement of effectiveness is based on 30 attributes that include the dimensions of input, process and output. The study uses a multi-criteria decision analysis approach that is supported by the software Rappoverty. The findings show that the pattern of zakat-based poverty alleviation program performs better on all attributes compared to the pattern of other programs. The sensitive leverage factors that determine performance status consist of: the suitability of the program to the needs of the target communities, socialization and education, inter-agency coordination, consistency in the implementation of the rules, the existence of public institutions to carry out and support the program, improvement of welfare recipients, as well as an increase in the number of beneficiaries. The findings of this study indicate that the pattern of poverty reduction programs based on zakat can be a useful model for policy makers in developing effective poverty alleviation programs. Keywords: zakat, performance status, leverage factors